2019
DOI: 10.1111/jpm.12550
|View full text |Cite
|
Sign up to set email alerts
|

Depression and intimate partner violence among urban Kenyan caregivers of children with disabilities

Abstract: Accessible summaryWhat is known on the subject? Caregivers of children with disabilities are at increased risk of experiencing interpersonal violence and its consequences; however, there is limited research targeting this population. This problem is understudied in Sub‐Saharan Africa. What this paper adds to existing knowledge? Study examines intimate partner violence and depression among men and women caregivers of children with disabilities. Study findings showed that while a higher proportion of wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In addition, compared with family nursing research in Finland, where family violence studies rank high as a focus area (Åstedt-Kurki, 2010), and interestingly counter to sub-Saharan Africa’s (SSA) high violence prevalence (Cools et al., 2005), there were only a scarce number of studies on family violence and abuse (Mugoya et al., 2020; Van Wijk et al., 2014). However, on the opposite side of the pendulum of violence, the classic African philosophy of Ubuntu encompassing compassion and humanity rooted in their beliefs, cultural influences and relationships, was only explored through three studies (Kahonde et al., 2019; Leuning et al., 2000; Temane et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with family nursing research in Finland, where family violence studies rank high as a focus area (Åstedt-Kurki, 2010), and interestingly counter to sub-Saharan Africa’s (SSA) high violence prevalence (Cools et al., 2005), there were only a scarce number of studies on family violence and abuse (Mugoya et al., 2020; Van Wijk et al., 2014). However, on the opposite side of the pendulum of violence, the classic African philosophy of Ubuntu encompassing compassion and humanity rooted in their beliefs, cultural influences and relationships, was only explored through three studies (Kahonde et al., 2019; Leuning et al., 2000; Temane et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…review noted that children exposed to IPV had a high prevalence of depressive symptoms, insecurity, and posttraumatic stress disorder, followed by adjustment/behavior problems and aggression, and declining academic performance. 33 Considering the potential mediation observed in this study, unexplored mother interpersonal and/or contextual factors within maternal depression and IPV should be explored in determining child socioemotional development. We also found that maternal mild to severe depressive symptoms were associated with lower child socioemotional development scores adjusted for maternal IPV.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 95%
“…Since these injuries predominate in low-resource environments where there is minimal road traffic safety, patients who sustain femur fractures can incur tremendous financial burden-as much as 88% of their pre-injury income 6 . While studies have examined the effect of treatment cost on patients and the costs of providing long-term care for chronic patients [7][8][9][10] , such as children with a disability 11,12 or the elderly, there is no literature on the burden of in-hospital informal caregivers who care for adults who had served as the primary household income earner up until their injury.…”
Section: Introductionmentioning
confidence: 99%